Innovative Educational Technologies in the Educational Process (Eurasian Research Bulletin, 2022)
In modern society, innovation technologies expand to almost every field of human activity, including such wide field as education. Innovation in education is a highly contentious issue. Education is sometimes perceived as one of the most conservative social systems and public policy fields.